Nanoceria distribution and effects are mouse-strain dependent. Issue 6 (2nd July 2020) - Yokel, Robert A.; Tseng, Michael T.; Butterfield, D. Allan; Hancock, Matthew L.; Grulke, Eric A.; Unrine, Jason M.; Stromberg, Arnold J.; Dozier, Alan K.; Graham, Uschi M.
Abstract: Prior studies showed nanoparticle clearance was different in C57BL/6 versus BALB/c mice, strains prone to Th1 and Th2 immune responses, respectively. Objective : Assess nanoceria (cerium oxide, CeO2 nanoparticle) uptake time course and organ distribution, cellular and oxidative stress, and bioprocessing as a function of mouse strain. Methods : C57BL/6 and BALB/c female mice were i.p. injected with 10 mg/kg nanoceria or vehicle and terminated 0.5 to 24 h later. Organs were collected for cerium analysis; light and electron microscopy with elemental mapping; and protein carbonyl, IL-1β, and caspase-1 determination. Results : Peripheral organ cerium significantly increased, generally more in C57BL/6 mice. Caspase-1 was significantly elevated in the liver at 6 h, to a greater extent in BALB/c mice, suggesting inflammasome pathway activation. Light microscopy revealed greater liver vacuolation in C57BL/6 mice and a nanoceria-induced decrease in BALB/c but not C57BL/6 mice vacuolation. Nanoceria increased spleen lymphoid white pulp cell density in BALB/c but not C57BL/6 mice. Electron microscopy showed intracellular nanoceria particles bioprocessed to form crystalline cerium phosphate nanoneedles. Ferritin accumulation was greatly increased proximal to the nanoceria, forming core-shell-like structures in C57BL/6 but even distribution in BALB/c mice. Conclusions : BALB/c mice were more responsive to nanoceria-induced effects, e.g. liver caspase-1 activation, reduced liver vacuolation, and increased spleen cell density. Nanoceria uptake, initiation of bioprocessing, and crystalline cerium phosphate nanoneedle formation were rapid. Ferritin greatly increased with a macrophage phenotype-dependent distribution. Further study will be needed to understand the mechanisms underlying the observed differences.